OPTIMALISASI LEMBAGA SEKOLAH BINAAN â€œSLB HARAPAN BUNDAâ€ SURABAYA DALAM MENINGKATKAN PENGETAHUAN DAN KETRAMPILAN GURU - Simanjuntak, Nensy Megawati; Arumtyas Puspitaning Padmasari; Muhajir; Haerussaleh; Nuril Huda; Ahmad Hatip (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
The community service activities carried out by the author and his team are one of the actions that originate from a sense of empathy and concern for social phenomena that occur in the Indonesian educational environment. One of these social phenomena is the problem of developing the Merdeka curriculum, especially in educational units that have the label Special Schools. Educators at Special Schools need direction regarding the implementation of independent curriculum development and all forms of school optimization. Community service activities aim to help Special Schools develop the Merdeka curriculum according to the situation and conditions of the school. Curriculum development will optimize school conditions. If school conditions are optimal, then automatically the teaching staff and students will feel optimal in developing their own wealth. The Special School targeted in this community service action is a school that focuses on special children with autism. Autism is a disorder that occurs in the brain and nerves, affecting the sufferer's behavior and attitude. Autistic children should not be underestimated or even ignored. Autistic children need us as fellow humans to support and love their condition. Keywords: Special School, Autism, Independent Curriculum